تعليم المفردات باستخدام كتاب "رأس سيراه" في المدرسة الدينية مفتاح الكرامة كراطان فاسوروان جاوى الشرقية - Edi Kurniawan Farid; Azizatul Firdausiyah (Al-Muyassar: Journal of Arabic Education, 2022)
AbstractTeaching vocabulary using the book "Ra'sun Sîrāh" in the Madrasah Dîniyyah Miftāh al-Karāmah Kraton Pasuruan East Java has advantages and teaching with it has characteristics. This research aims to (a) describe the advantages and disadvantages of the book "Ra'sun Sîrāh" for teaching vocabulary and (b) to explain the teaching of vocabulary by using it in this school. This qualitative research uses observation, interviews, and documentation in data collection. And the method of analyzing data uses interactive analysis of Mills and Huberman and testing its validity by triangulating the sources. The results of this research are the advantages of the book "Ra'sun Sîrāh" in teaching vocabulary (1) The book contains primer vocabulary, so it is beneficial for students who want to learn Arabic at the beginner level. Arabic vocabulary with its Javanese meaning is written and formed into poetry verses (naẕm). (3) students can recite it by singing the rhythms so that it is easier for students to learn vocabulary, and students can learn with pleasure. On the other hand, there are some disadvantages while using this book, (1) the students had difficulty understanding the meaning of the Javanese vocabulary in the naẕm. (2) The students had difficulty reading the meaning of the vocabulary using the writing "pego". (3) The students faced heavy and bored with the repetition method. (4) The teacher faced difficulty in developing the memorization method. Teaching vocabulary was implemented using this book through the singing method, the simulation and memorization method, and the questions and answers method. مستخلص البحثتعليم المفردات باستخدام كتاب "رأس سيراه" في المدرسة الدينية مفتاح الكرامة كراطان فاسوروان جاوى الشرقية له مزايا والتعليم به له خصائص. هدف هذا البحث إلى (أ) وصف المزايا والعيوب لدى كتاب "رأس سيراه" لتعليم المفردات و(ب) كشف تعليم المفردات باستخدامه في هذه المدرسة. استخدم هذا البحث الكيفي الملاحظة والمقابلة والتوثيق في جمع البيانات. وطريقة تحليل البيانات بالتحليل التفاعلي لميلس وهوبرمان واختبار صحتها بتثليث المصادر. ونتائج هذا البحث هي إن مزايا كتاب "رأس سيراه" في تعليم المفردات (1) يحتوي الكتاب على مفردات أساسية لذلك فهي مفيدة جدًا للتلاميذ الذين يرغبون في تعلم اللغة العربية على مستوى المبتدئين. (2) يتم ترتيب المفردات مع معناها الجاوي وتشكيلها في نظم بسيط. (3) يمكن للتلاميذ تلاوة النظم من خلال غناء النظم حتى يسهل على التلاميذ تعلم المفردات، كما يمكن للتلاميذ التعلم بكل سرور. وبجانب آخر هناك بعض العيوب من استخدام هذا الكتاب وهي (1) كان التلاميذ لهم صعوبة في فهم معنى الجاوية من المفردات في النظم. (2) كان التلاميذ لهم صعوبة في قراءة معنى المفردات باستخدام كتابة "فيكو". (3) يشعر التلاميذ بالثقل والملل من طريقة التلقين المتبعة. (4) واجه المعلم صعوبة في تطوير طريقة الحفظ. وتم تنفيذ تعليم المفردات باستخدام هذا الكتاب عن طريقة الغناء، وطريقة المحاكاة والحفظ، وطريقة الأسئلة والأجوابة.